Peran Guru Sekolah Minggu dalam Mendukung Perkembangan Sosial-Emosional Anak Usia Dini Relevansinya Bagi PAUD Arastamar Kids Pekanbaru - Aben Tuke Banamtuan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This community service activity was carried out to support and strengthen the role of Sunday school teachers in fostering the social and emotional development of preschool children. Early social experiences generally begin in the family, but schools and religious education institutions also play a significant role in shaping children’s abilities to interact, share, and communicate effectively. The program was implemented at PAUD Arastamar Kids Pekanbaru through participatory activities that involved teachers and children. The approach emphasized interactive methods such as giving praise, teaching simple religious values, playing games, and organizing creative learning activities. Examples included origami-making, group singing, storytelling, and encouraging children to share crayons or toys with their peers. These activities not only created a fun and engaging learning atmosphere but also helped children develop empathy, cooperation, and independence. Teachers were guided to consistently integrate these activities into their routines to maximize the positive outcomes. The results of this service showed that Sunday school teachers could effectively encourage positive social-emotional growth by combining religious teachings with play-based and interactive learning. In conclusion, the program provided valuable contributions to strengthening the capacity of teachers while creating a supportive environment for children to interact positively and independently with others.